Risk of Depressive Disorders Following Myasthenia Gravis: A Nationwide Population-Based Retrospective Cohort Study - Chu, Hsuan-Te; Tseng, Chih-Chieh; Liang, Chih-Sung; Yeh, Ta-Chuan; Hu, Li-Yu; Yang, Albert C.; Tsai, Shih-Jen; Shen, Cheng-Che (Frontiers in Psychiatry, 2019)
The chronic autoimmune disease myasthenia gravis (MG) is characterized with fluctuating muscle weakness which can lead to a large amount of stress in the patient. The current investigation plans to assess the risk of depressive disorders in MG patients. A retrospective cohort study of patients ageing from 20 year and older and also newly diagnosed with MG between January 1st, 2000 and December 31st, 2008 was conducted from the National Health Insurance Research Database (NHIRD) in Taiwan. Observations of all 349 MG patients and 1,396 control individuals were made until diagnosed with a depressive disorder by a psychiatrist, death, or until December 31st, 2013. A range of comorbidities were found, such as coronary artery disease, hypertension, diabetes mellitus, dyslipidemia, with cerebrovascular disease being reported more frequently in MG patients in comparison to control subjects. After adjustment of patients’ sex, age, urbanization, comorbidities, and monthly income, results indicated that MG individuals are 1.94 times more at risk (95% confidence interval [CI], 1.15- 3.27, P = .014) of developing depressive disorders than controls. This showed an increased risk in the development of depressive disorders in people with MG. Thus, depressive symptoms in MG patients should be regularly assessed.